Thermal and magnetic properties of nanostructured densified ferrimagnetic composites with graphene - graphite fillers. (15th March 2017) - Ramirez, S.; Chan, K.; Hernandez, R.; Recinos, E.; Hernandez, E.; Salgado, R.; Khitun, A.G.; Garay, J.E.; Balandin, A.A.
Abstract: We report the results of an experimental study of thermal and magnetic properties of nanostructured ferrimagnetic iron oxide composites with graphene and graphite fillers synthesized via the current activated pressure assisted densification. The thermal conductivity was measured using the laser-flash and transient plane source techniques. It was demonstrated that addition of 5 wt.% of equal mixture of graphene and graphite flakes to the composite results in a factor of × 2.6 enhancement of the thermal conductivity without significant degradation of the saturation magnetization. The microscopy and spectroscopic characterization reveal that sp 2 carbon fillers preserve their crystal structure and morphology during the composite processing. The strong increase in the thermal conductivity was attributed to the excellent phonon heat conduction properties of graphene and graphite. The results are important for energy and electronic applications of the nanostructured permanent magnets. Graphical abstract: Highlights: We report on synthesis of nanostructured ferrimagnetic iron oxide composites with graphene - graphite fillers for improved heat conduction in permanent magnets. It was demonstrated that addition of graphene and graphite fillers results in × 2.6 increase of the thermal conductivity without significant degradation of magnetization. Strong increase in the thermal conductivity of magnetic composites was attributed to the excellent heat conduction properties of graphene and graphite.